Development of the Nine-Ball Skills Test to discriminate elite and high-level amateur golfers - Robertson, S. J.; Burnett, A. F.; Newton, R. U.; Knight, P. W. (Journal of Sports Sciences, 2012)
Currently, there is a lack of appropriate skill assessments available for use in golf. The aim of this study was to examine the discriminative validity and the test-retest reliability of the newly developed "Nine-Ball Skills Test". Participants of two ability levels (elite, n = 14; high-level amateur, n = 16) each hit nine golf shots of differing combinations of trajectory (straight, fade, draw) and height (normal, high, low) at an individually determined target area. Each shot was scored on its percent error index from the target and whether it achieved the maximum height as required. Participants completed the test twice using a 5-iron club. The elite group scored significantly higher (P < 0.05) than the amateur group for both the first and second rounds of the test as well as the combined scores. The between-round test-retest reliability was deemed to be not acceptable, thus we propose that the test's protocol should include use of the two rounds as standard. Due to the importance of ball striking and flight control to performance in golf, the Nine-Ball Skills Test is appropriate for providing a measure of this skill component in elite and high-level amateur golfers.